Effect of Co3+ substitution on electro-magnetic properties of Pr0.75Na0.25mno3 and Nd0.75Na0.25mno3 manganites - Ab Mannan, Nurhabibah Nabilah; Razali, Sufia Aqilah; Shamsuddin, Suhadir; Noh, Mohamad Zaky; Mohamed, Zakiah (Science Publishing Corporation, 2018)
This paper reports influences of cobalt (Co) substituted at Mn-site of Pr0.75Na0.25Mn1-xCoxO3 and Nd0.75Na0.25Mn1-yCoyO3 on structure, electrical transport and magnetic properties. All of the samples were prepared via standard solid state reaction method. X-ray diffraction measurement indicates that all samples were crystallized in an orthorhombic structure (space group Pnma). Resistivity measurement displays the x = 0 sample manifests an insulator behavior while metal-insulator transition was found at 108 K and 84 K for x = 0.02 and 0.05 respectively for Pr0.75Na0.25Mn1-xCoxO3. On the other hand, all of the samples for Nd0.75Na0.25Mn1-yCoyO3 showed insulator behavior down to low temperature and analysis of the resistivity change with respect to temperature, dlnρ/dT -1 versus T reveals a slope changes of resistivity have been recorded. Two obvious peaks were recorded from the analysis for y = 0.02 and 0.05 which can be suggested to the existence of charge order transition at the vicinity. For magnetic properties, x = 0 sample showed a paramagnetic-antiferromagnetic transition and further substitution of Co, x = 0.02 and 0.05, induce the paramagnetic-ferromagnetic transition and antiferromagnetic arrangement respectively. Meanwhile, further substitution of Co, y = 0.02 and 0.05 indicate antiferromagnetic transition with increasing TN as Co increased.